2022
DOI: 10.1027/1015-5759/a000646
|View full text |Cite
|
Sign up to set email alerts
|

Not Only Reliability!

Abstract: Abstract. The measurement of math anxiety in adults is justified based on observations that math anxiety in parents and teachers predicts children’s math anxiety and achievement. Although there are many very good math anxiety measures intended for children and adolescents, their usefulness (e.g., AMAS, MARS) for adults is debatable. The most important objection against using these scales for adults is their ecological validity. The measurement of anxiety associated with math tests, classes, teachers, and homew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The first was the Abbreviated Math Anxiety Scale (AMAS; Hopko et al, 2003), consisting of 9 items divided into two subscales: testing (AMAS-T, α = .88) and learning (AMAS-L, α = .90) math anxiety (4 and 5 items, respectively). The second was the Math Anxiety Questionnaire for Adults (MAQA; Szczygieł, 2022), consisting of 19 items (α = .95) and measures math anxiety related to math problem-solving. Third was the Single-Item Math Anxiety Scale (SIMA; Núñez-Peña et al, 2014), including the question, "On a scale from 1 to 10, how math anxious are you?".…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first was the Abbreviated Math Anxiety Scale (AMAS; Hopko et al, 2003), consisting of 9 items divided into two subscales: testing (AMAS-T, α = .88) and learning (AMAS-L, α = .90) math anxiety (4 and 5 items, respectively). The second was the Math Anxiety Questionnaire for Adults (MAQA; Szczygieł, 2022), consisting of 19 items (α = .95) and measures math anxiety related to math problem-solving. Third was the Single-Item Math Anxiety Scale (SIMA; Núñez-Peña et al, 2014), including the question, "On a scale from 1 to 10, how math anxious are you?".…”
Section: Methodsmentioning
confidence: 99%
“…A multidimensional construct of math anxiety (MA) is defined as "[...] a feeling of tension and anxiety that interferes with the manipulation of numbers and the solving of mathematical problems in a wide variety of ordinary life and academic situations" (Richardson & Suinn, 1972, p. 551). Various types of MA are differentiated (e.g., learning anxiety, testing anxiety, problem-solving anxiety), however, previous research results indicate that MA dimensions are strongly and positively related to each other (Szczygieł, 2022). Although MA is not the only emotion accompanying learning mathematics, it is the most studied one.…”
Section: Introductionmentioning
confidence: 97%
“…We used the Math Anxiety Questionnaire for Adults (MAQA; Szczygieł, 2022). For each of the 19 items, participants are asked to declare the level of anxiety that they would feel in hypothetical situations involving numbers.…”
Section: Math Anxietymentioning
confidence: 99%
“…Research on mathematics anxiety is relatively new [3], and a clear picture of the prevalence distribution across age ranges and how prevalence changed over time is still missing [5]. Additionally, a formal set of criteria to assess high mathematics anxiety levels has not yet been defined [10], and construct validity may vary across age [5,11]. However, prevalence estimates report high levels of mathematics anxiety among the 2%-6% of secondary students [12], 30%-68% among young adults [13,14], 11% among university students [15], and recent epidemiological models predicted that 70% of undergraduate students would suffer from high mathematics anxiety levels in the next few years [16].…”
Section: Introductionmentioning
confidence: 99%
“…The strong correlations between the various mathematics anxiety assessment tools in the (young) adult population reflect their undisputed reliability [63,64]. However, recent research showed that non-STEM students could be misrepresented because of the limited construct validity of such assessment tools for this population group [11].…”
mentioning
confidence: 99%